PELATIHAN PADUAN SUARA MAHASISWA STAIN MANDAILING NATAL PADA HARI AMAL BAKTI (HAB) KEMENTERIAN AGAMA KE 76 TAHUN 2022 - Wahyu Fitrina Defi (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Optimizing the interests and talents of students on campuses with Islamic nuances needs to be done and there are no restrictions on this. This is also supported by the slogan of the Ministry of Religion which is moderate in religion with the meaning that everything in the implementation of organizational activities should be based on fair and equitable principles and not take sides on one side. It is necessary to explore the interests and talents of students in the field of choir. Its existence as an important activity in every event carried out by the campus places it as a priority activity position and training needs to be carried out on an ongoing basis. However, the problem is that the choir team at STAIN Mandailing Natal does not always stay because the team consisting of students always changes every year with different characteristics. Therefore, this choir training needs to be carried out routinely with the stages of planning, organizing, implementing, and evaluating. The result of this dedication is the ability to harmonize the STAIN Mandailing Natal Student Choir in the 2022 Ministry of Religion HAB. In addition to that, students are also able to collaborate with local art groups, namely the MAN 1 Mandailing Natal Marching Band team.